Magnetic composite powder and preparation method thereof and application in degradation of methylene blue wastewater

By preparing magnetic composite powder, using its magnetic properties and catalytic effects, the problems of existing adsorbent materials and carbon emissions are solved, and efficient degradation and environmentally friendly recycling of methylene blue wastewater are achieved.

CN118807693BActive Publication Date: 2025-02-14NANCHANG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411311877.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-02-14
Estimated Expiration
2044-09-20

AI Technical Summary

Technical Problem

Existing adsorbent materials such as activated carbon have difficulties in recycling and carbon emission problems when treating methylene blue wastewater, making it difficult to effectively degrade methylene blue wastewater.

Method used

Magnetic composite powder is used to form composite powder by mixing and crushing the oil tea shell, modified powder and natural rubber resin in a mixer, and heating it in a non-oxidizing atmosphere of 500-700°C to form composite powder and fill it in a magnetic field. Magnetic, imparting its magnetic properties to allow recycling and degradation of methylene blue wastewater.

Benefits of technology

It realizes efficient degradation of methylene blue wastewater and rapid recovery of magnetic composite powders, avoids secondary pollution, and does not emit carbon emissions during the preparation process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118807693B_ABST
    Figure CN118807693B_ABST
Patent Text Reader

Abstract

The present invention provides a magnetic composite powder, a preparation method and an application in the degradation of methylene blue wastewater, and relates to the technical field of wastewater treatment. The preparation method provided by the present invention comprises the following steps: mixing and crushing camellia shell, modified powder and natural rubber resin in an open mill, heating in a non-oxidizing atmosphere at 500-700°C, crushing in a pulverizer and then sieving to obtain a composite powder, and magnetizing the composite powder in a magnetic field to obtain a magnetic composite powder; the modified powder comprises modified MFe 12 O 19 , wherein M is at least one of Ba and Sr. The present invention can give the composite powder magnetic properties by compounding the modified powder, thereby facilitating the recovery of the composite powder. In addition, the magnetic composite powder has high efficiency in degrading methylene blue, and no carbon emissions are emitted during the preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of wastewater treatment, and in particular to a magnetic composite powder and a preparation method thereof, and application thereof in the degradation of methylene blue wastewater. Background Art

[0002] A dye is a colored compound that absorbs electromagnetic energy in the visible range. Dye molecules have both chromophores (delocalized electron systems with conjugated double bonds) and auxochromes (electron-withdrawing or electron-donating groups that enhance color). Chromophores such as –C=C–, –C=N, –C=O, –N=N–, –NO2, and quinone rings give dye molecules their color, while auxochromes such as -NH2, -COOH, -OH, etc. enhance the color of chromophores by changing the total energy of the molecular system’s electron cloud.

[0003] In recent years, with the rapid development of the printing and dyeing industry, the discharge of printing and dyeing wastewater, mainly azo dyes, has caused serious water resource pollution. Azo dyes can cause an imbalance in the organic-inorganic chemical components in the environment and affect the biological components in the water. When the dye is mixed with water, the light penetration efficiency inside the water system will be reduced, thus affecting the aquatic ecosystem. The toxic substances present in azo dyes will enter the bodies of fish or other aquatic animals and be further absorbed by the human body, causing high blood pressure, sporadic disorders, cramps, etc., with a long-term impact. In addition, benzidine-based azo dyes have been considered to be carcinogens in human bladders and tumorigenic substances in laboratory animals. It can also cause liver cancer, spleen sarcoma, nuclear abnormalities in experimental animals, and chromosomal aberrations in mammalian cells.

[0004] Methylene blue is a widely used water-soluble azo dye. This substance forms a monovalent cationic quaternary ammonium salt ion group in water, has a high chromaticity, and is difficult to be biodegraded. After entering the environment, dye wastewater containing methylene blue will affect the photosynthesis of aquatic plants, destroy the ecological balance, and pollute the environment. Therefore, it is necessary to treat wastewater containing organic dyes such as methylene blue.

[0005] Common wastewater treatment technologies include adsorption, membrane separation, electrolysis, advanced oxidation and biological methods. Among them, adsorption has the advantages of flexible process, simple operation and high efficiency, and has been widely used. However, common adsorption materials such as activated carbon have prominent problems such as difficulty in recycling and carbon emissions in the preparation process. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention

[0006] The purpose of the present invention is to provide a magnetic composite powder, a preparation method and an application in the degradation of methylene blue wastewater. By compounding the modified powder, the composite powder can be given magnetism, which is beneficial to the recovery of the composite powder. In addition, the magnetic composite powder has high efficiency in degrading methylene blue and no carbon emissions are emitted during the preparation process.

[0007] In the first aspect, the present invention provides a method for preparing a magnetic composite powder, comprising mixing and crushing camellia oleifera shell, modified powder and natural rubber resin in an open mill, heating in a non-oxidizing atmosphere at 500-700°C, crushing in a pulverizer and sieving to obtain a composite powder, and magnetizing the composite powder in a magnetic field to obtain a magnetic composite powder; the modified powder comprises modified MFe 12 O 19 , wherein M is at least one of Ba or Sr.

[0008] The preparation method provided by the present invention is that the oil tea shell is a natural biomass resource, which is not only abundant and renewable, but also has a unique chemical structure that can provide favorable conditions for the subsequent degradation process. At the same time, the modified powder is introduced as a magnetic component, and can be quickly recovered by a magnetic field after wastewater treatment, thereby avoiding secondary pollution of the wastewater. At the same time, the modified powder not only has good magnetic properties, but also can play a catalytic role in the degradation process to accelerate the degradation of dye molecules. In addition, the addition of natural rubber resin not only enhances the structural stability of the composite powder, but also provides a guarantee for its dispersibility and operability in practical applications.

[0009] Optionally, the modified MFe 12 O 19 The preparation method comprises: 12 O 19 After soaking in tetraethyl orthosilicate for modification, separation and drying were performed to obtain modified MFe. 12 O 19 .

[0010] Optionally, MFe 12 O 19 Soak in tetraethyl orthosilicate for modification for 20-40 minutes.

[0011] Optionally, MFe 12 O 19 Modified by soaking in tetraethyl orthosilicate at 20-30℃.

[0012] Optionally, MFe 12 O 19 After passing through a 100-200 mesh sieve, it is immersed in tetraethyl orthosilicate for modification.

[0013] Optionally, MFe 12 O 19The modification is carried out by immersion in tetraethyl orthosilicate by mechanical mixing, wherein the mechanical mixing includes at least one of stirring and ultrasound.

[0014] Optionally, the separation includes one of filtration separation and suction filtration separation.

[0015] Optionally, the separated MFe 12 O 19 Drying is carried out at 100-150°C.

[0016] Optionally, the mass ratio of the camellia oleifera shell to the modified powder is (70-50): (30-50).

[0017] Optionally, the mass ratio of the natural rubber resin to the tea oil shell is (10-30):100.

[0018] Optionally, the natural rubber resin is not vulcanized.

[0019] Optionally, the camellia oleifera shell, the modified powder and the natural rubber resin are mixed and crushed in an open mill at 20-250° C. for 0.5-1.5 h.

[0020] Optionally, the non-oxidizing atmosphere includes at least one of a nitrogen atmosphere and an inert atmosphere.

[0021] Optionally, semi-cracking is carried out in a non-oxidizing atmosphere at 500-700° C. for 0.5-1.5 h.

[0022] Optionally, in a non-oxidizing atmosphere, the temperature is increased to 500-700° C. at a rate of 1-10° C. / min.

[0023] Optionally, the particle size of the composite powder is 50µm-150µm.

[0024] Optionally, the composite powder is magnetized in a 0.5-2T magnetic field environment.

[0025] Optionally, the method comprises the following steps: mixing and crushing camellia oleifera shells, modified powder and natural rubber resin in an open mill to obtain composite rubber particles; heating the composite rubber particles in a non-oxidizing atmosphere of 500-700°C, crushing them in a grinder and then sieving them to obtain composite powder; and magnetizing the composite powder in a magnetic field to obtain magnetic composite powder.

[0026] Optionally, the oil-tea camellia shell, modified powder and natural rubber resin are mixed and crushed in an open mill, and then granulated through a 30-200 mesh sieve to obtain composite rubber particles.

[0027] In a second aspect, the present invention further provides a magnetic composite powder prepared by any of the above optional preparation methods.

[0028] In a third aspect, the present invention further provides an application of a magnetic composite powder prepared by any of the above optional preparation methods in the degradation of methylene blue wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 A flowchart of the method for preparing magnetic composite powder provided by the present invention;

[0030] Figure 2 The following is a TGA curve diagram of the composite colloid particles during pyrolysis in some embodiments of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.

[0032] The invention provides a method for preparing a magnetic composite powder, comprising the steps of mixing and crushing camellia oleifera shells, modified powder and natural rubber resin in an open mill, heating the mixture in a non-oxidizing atmosphere at 500-700°C, crushing the mixture in a pulverizer, and sieving the mixture to obtain a composite powder, and magnetizing the composite powder in a magnetic field to obtain a magnetic composite powder.

[0033] In fact, using an open mill to mix the camellia oleifera shell, modified powder and natural rubber resin can not only crush the camellia oleifera shell, but also make the modified powder and the camellia oleifera shell evenly dispersed in the natural rubber resin, so that the mixture of the three forms a uniform mixed resin material.

[0034] In some embodiments, the source of the camellia oleifera shell used can be natural camellia oleifera shell, which can not only recycle biomass resources, but also utilize the rich resource reserves and renewable properties of camellia oleifera shell to reduce the manufacturing cost of magnetic composite powder. In addition, the unique chemical structure on the surface of camellia oleifera shell can also provide favorable conditions for the interpretation of methylene blue wastewater.

[0035] In some embodiments, the natural rubber resin used is not vulcanized, so as to avoid the introduction of impurities such as sulfur into the magnetic composite powder, thereby effectively ensuring the degradation efficiency of the prepared magnetic composite powder. Specifically, the natural rubber resin used can be Malaysian 1# smoked rubber.

[0036] In some embodiments, when the camellia oleifera shells, modified powders and natural rubber resins are mixed and crushed in an open mill, the camellia oleifera shells and the modified powders may be mechanically mixed in advance, which can improve the mixing uniformity of the camellia oleifera shells and the modified powders, thereby facilitating uniform mixing in the open mill.

[0037] Specifically, when the camellia oleifera shell and the modified powder are mixed, the mass ratio of the camellia oleifera shell to the modified powder is (70-50): (30-50). In fact, by adjusting the mixing ratio of the camellia oleifera shell and the modified powder, the overall magnetic properties of the magnetic composite powder and the content of the camellia oleifera shell therein can be effectively adjusted, thereby adjusting the degradation and adsorption performance of the magnetic composite powder on methylene blue wastewater.

[0038] In fact, the mass ratio of camellia oleifera shell in the mixture of camellia oleifera shell and modified powder is 50%-70%. When the content of camellia oleifera shell is greater than 70%, the magnetism of the magnetic composite powder will be reduced, which is not conducive to magnetic separation after wastewater degradation. When the content of camellia oleifera shell is less than 50%, the degradation and adsorption capacity of the magnetic composite powder for methylene blue wastewater will be reduced.

[0039] Specifically, when the camellia oleifera shell, the modified powder and the natural rubber resin are mixed, the mass ratio of the natural rubber resin to the camellia oleifera shell is (10-30): 100. In fact, by adjusting the amount of the natural rubber resin, the content of the camellia oleifera shell in the magnetic composite powder can be avoided from being reduced while the modified powder and the camellia oleifera shell are bonded and mixed.

[0040] In some embodiments, the camellia oleifera shell, modified powder and natural rubber resin are mixed and crushed in an open mill at 20-250° C. for 0.5-1.5 h, which is conducive to uniform crushing and blending of the three raw materials in the open mill.

[0041] In fact, the modified powders used include modified MFe 12 O 19 , wherein M is at least one of Ba and Sr. Specifically, the modified powder includes modified BaFe 12 O 19 , modified SrFe 12 O 19 At least one of the above can impart magnetic properties to the camellia oleifera shell by compounding the modified powder with the camellia oleifera shell, which is beneficial for recovery in a magnetic field environment during post-processing. In addition, the degradation of methylene blue molecules can also be catalyzed.

[0042] Specifically, the preparation method of the modified powder comprises: 12 O 19 After soaking in tetraethyl orthosilicate for modification, separation and drying were performed to obtain modified MFe. 12 O 19 By using MFe12 O 19 The powder is immersed in tetraethyl orthosilicate, which can fully infiltrate MFe 12 O 19 The surface of the powder forms a liquid coating on the surface of the powder. The coating will dehydrate in the subsequent drying stage to further form a SiO2 solid coating. The SiO2 solid coating becomes MFe 12 O 19 The interface between the powder, tea oil shell and natural rubber resin prevents MFe 12 O 19 The composition of the powder changes and enhances the MFe 12 O 19 The bonding properties of powder and camellia oleifera shell.

[0043] In some embodiments, when preparing the modified powder, MFe 12 O 19 Soak in tetraethyl orthosilicate for 20-40 minutes to promote the tetraethyl orthosilicate to MFe 12 O 19 The full infiltration of MFe 12 O 19 During the soaking process, mechanical mixing can be used to 12 O 19 The mixture is uniformly mixed with ethyl orthosilicate, such as by mechanical stirring, ultrasonic mixing, oscillating mixing, etc.

[0044] In some embodiments, when preparing the modified powder, MFe 12 O 19 Soak in 20-30℃ ethyl orthosilicate. 12 O 19 During the immersion process, the higher the temperature of ethyl orthosilicate, the more it can promote the 12 O 19 However, from the perspective of energy consumption and experimental convenience, immersion modification at room temperature can also achieve the same modification effect.

[0045] In some embodiments, when preparing the modified powder, MFe 12 O 19 After passing through a 100-200 mesh sieve, it is placed in tetraethyl orthosilicate for soaking. Through pre-screening, small-sized MFe particles can be screened out. 12 O 19 , thereby effectively improving MFe 12 O 19 The specific surface area of ​​​​ethyl orthosilicate is increased 12 O 19 modification effect.

[0046] In some embodiments, when preparing the modified powder, when MFe 12 O 19 After soaking in ethyl orthosilicate, the MFe2O3 can be separated by common solid-liquid separation methods including filtration separation and suction filtration separation. 12 O 19 In fact, when drying, the separated MFe 12 O 19 Dry in a drying oven at 100-150°C to constant weight.

[0047] In fact, when the mixed and crushed materials are heated in a non-oxidizing atmosphere at 500-700°C, the non-oxidizing atmosphere used includes at least one of a nitrogen atmosphere and an inert atmosphere. In fact, by using a non-oxidizing atmosphere for protection, carbonization of natural rubber resin and camellia oleifera shells in a high temperature environment can be effectively avoided. In addition, when treated within this temperature range, the surface of the camellia oleifera shells undergoes semi-cracking to form a unique chemical structure, which is beneficial to the degradation of methylene blue wastewater. Specifically, the mixed and crushed materials are kept in a non-oxidizing atmosphere at 500-700°C for 0.5-1.5h for semi-cracking.

[0048] In some embodiments, the mixed and crushed materials are placed in an atmosphere furnace in advance, and the atmosphere furnace is replaced multiple times with a non-oxidizing gas at room temperature to make the atmosphere furnace a non-oxidizing atmosphere. The atmosphere furnace is then heated to 500-700°C at a rate of 1-10°C / min.

[0049] In some embodiments, the composite powder after semi-cracking in a non-oxidizing atmosphere is crushed by a crusher, which is beneficial to further reduce the particle size of the powder, thereby increasing the specific surface area of ​​the composite powder and increasing the number of surface active sites. Specifically, the particle size of the composite powder obtained after crushing is 50µm-150µm.

[0050] In some embodiments, the composite powder is magnetized in a 0.5-2T magnetic field environment to impart magnetic properties to the composite powder.

[0051] In some embodiments, see Figure 1 The method for preparing the magnetic composite powder provided by the present invention comprises the following steps:

[0052] S1, mixing and grinding the camellia oleifera shell, the modified powder and the natural rubber resin in an open mill to obtain composite rubber particles;

[0053] S2, heating the composite granules in a non-oxidizing atmosphere at 500-700°C, crushing them in a pulverizer, and then sieving them to obtain composite powder;

[0054] S3. Magnetizing the composite powder in a magnetic field to obtain magnetic composite powder.

[0055] In fact, when executing step S1, after mixing and crushing in an open mill, granulation is performed and the granules are passed through a 30-200 mesh sieve to obtain composite rubber particles.

[0056] In some embodiments, the composite particles in step S2 are tested during the heating process using a synchronous thermal analyzer STA449 F5, and the reaction conditions are a nitrogen flow rate of 20 mL / min, a composite particle mass of 5 mg, and a heating rate of 10°C / min. The test results are as follows: Figure 2 As shown. Figure 2 It can be seen from the TGA curve in that at 255.3℃-335.3℃, the composite colloid particles experience severe weight loss, which is due to the volatilization of solvent molecules in the porous structure of the composite colloid particles, but the phase structure remains unchanged, and at 335.3℃-438.2℃, the composite colloid particles continue to lose weight, which is because the organic molecular framework begins to crack and an exothermic reaction also occurs. At 438.2℃-580℃, the composite colloid particles undergo deep cracking, with an obvious exothermic peak at 438.2℃, and the quality remains stable at 580℃, which indicates that the molecular framework of the composite powder has completed cracking and is in a relatively stable state.

[0057] The present invention also provides an application of using the magnetic composite powder prepared in any of the above embodiments to degrade methylene blue wastewater, by adding the magnetic composite powder into the methylene blue wastewater and stirring and mixing, and after the wastewater is completely decolorized, transferring the magnetic composite powder into a magnetic field environment to recover the magnetic composite powder. In fact, the amount of the magnetic composite powder added to the methylene blue wastewater is positively correlated with the concentration of the methylene blue.

[0058] Preparation Example 1

[0059] This preparation example 1 provides a modified BaFe 12 The preparation method of O9 comprises: passing BaFe 12 O 19 After adding tetraethyl orthosilicate (CAS: 78-10-4) to the powder (CAS: 11138-11-7), the mixture was stirred at room temperature of 25°C for 30 minutes, the powder was filtered, and then dried in a drying oven at 130°C for 1 hour to obtain modified BaFe 12 O9.

[0060] Preparation Example 2

[0061] This preparation example 2 provides a modified SrFe 12 The preparation method of O9 comprises: passing SrFe through a 150-mesh sieve; 12After adding tetraethyl orthosilicate (CAS: 78-10-4) to O9 powder (CAS: 12023-91-5), the mixture was stirred for 30 min at room temperature of 25 °C, the powder was filtered, and then dried in a drying oven at 130 °C for 1 h to obtain modified SrFe 12 O9.

[0062] Example 1

[0063] This embodiment 1 provides a method for preparing a magnetic composite powder, comprising the following steps:

[0064] S1, tea shell, modified BaFe 12 O9 (Preparation Example 1) was mixed with natural rubber resin in a mass ratio of 70:30:7, and the mixture was mixed in an open rubber mixer at room temperature for 1 hour, and then granulated and sieved through a 150-mesh sieve to obtain composite rubber granules;

[0065] S2, keeping the composite particles at 500°C in a nitrogen atmosphere for 1 hour and then cooling them to obtain a black intermediate powder;

[0066] S3. Magnetizing the intermediate powder in a 1.0T magnetic field to obtain a magnetic composite powder.

[0067] Example 2

[0068] This embodiment 2 provides a method for preparing a magnetic composite powder, comprising the following steps:

[0069] S1, tea shell, modified SrFe 12 O9 (Preparation Example 2) was mixed with natural rubber resin at a mass ratio of 50:50:5, and the mixture was mixed in an open rubber mixer at room temperature for 1 hour, and then granulated and sieved through a 150-mesh sieve to obtain composite rubber granules;

[0070] S2, keeping the composite particles at 700°C in a nitrogen atmosphere for 1 hour and then cooling them to obtain a black intermediate powder;

[0071] S3. Magnetizing the intermediate powder in a 1.0T magnetic field to obtain a magnetic composite powder.

[0072] Example 3

[0073] This embodiment 3 provides a method for preparing a magnetic composite powder, comprising the following steps:

[0074] S1, tea shell, modified BaFe 12 O 19 (Preparation Example 1) After mixing with natural rubber resin at a mass ratio of 70:30:14, the mixture was mixed in an open rubber mixer at room temperature for 1 hour, granulated and sieved through a 150-mesh sieve to obtain composite rubber particles;

[0075] S2, keeping the composite particles at 600°C in a nitrogen atmosphere for 1 hour and then cooling them to obtain a black intermediate powder;

[0076] S3. Magnetizing the intermediate powder in a 2.0T magnetic field to obtain a magnetic composite powder.

[0077] Performance Testing

[0078] Deionized water was used to prepare methylene blue wastewater with a mass concentration of 250 mg / mL, and 1.0 g of the magnetic composite powders prepared in Examples 1 to 3 were respectively put into 10 mL of methylene blue wastewater. After stirring and mixing for 30 minutes, a magnet was used to adsorb the magnetic composite powders at the bottom of the wastewater container, and the wastewater was separated to observe complete decolorization, which indicates that the magnetic composite powders prepared by the present invention have good degradation and decolorization performance for methylene blue wastewater.

[0079] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may also have other embodiments and may be implemented or realized in a variety of ways.

Claims

1. A method for preparing a magnetic composite powder, characterized in that: The oil tea shell, modified powder and natural rubber resin are mixed and crushed in an open mill, and then kept in a non-oxidizing atmosphere at 500-700°C for 0.5-1.5h for semi-cracking, and then crushed in a pulverizer and sieved to obtain a composite powder, and the composite powder is magnetized in a magnetic field to obtain a magnetic composite powder; the modified powder includes modified MFe 12 O 19 , wherein M is at least one of Ba and Sr, and the modified MFe 12 O 19 The preparation method comprises: 12 O 19 After soaking in tetraethyl orthosilicate for modification, separation and drying were performed to obtain modified MFe. 12 O 19 The mass ratio of the camellia oleifera shell to the modified powder is (70-50): (30-50), the mass ratio of the natural rubber resin to the camellia oleifera shell is (10-30): 100, and the natural rubber resin has not been vulcanized.

2. The preparation method according to claim 1, characterized in that: Will MFe 12 O 19 Soak in tetraethyl orthosilicate for 20-40 minutes; and / or, MFe 12 O 19 Soak in ethyl orthosilicate at 20-30℃ for modification; and / or, MFe 12 O 19 After passing through a 100-200 mesh sieve, soak and modify in tetraethyl orthosilicate; and / or, MFe 12 O 19 Mechanical mixing and soaking in tetraethyl orthosilicate for modification, wherein the mechanical mixing includes at least one of stirring and ultrasound; And / or, the separation comprises one of filtration separation and suction filtration separation; and / or, the separated MFe 12 O 19 Drying is carried out at 100-150°C.

3. The preparation method according to claim 1, characterized in that: The camellia oleifera shell, modified powder and natural rubber resin are mixed and crushed in an open mill at 20-250° C. for 0.5-1.5 h.

4. The preparation method according to claim 1, characterized in that: The non-oxidizing atmosphere includes at least one of a nitrogen atmosphere and an inert atmosphere; and / or, in a non-oxidizing atmosphere, heating to 500-700° C. at a rate of 1-10° C. / min.

5. The preparation method according to claim 1, characterized in that: The particle size of the composite powder is 50µm-150µm; And / or, the composite powder is magnetized in a 0.5-2T magnetic field environment.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: mixing and crushing camellia oleifera shell, modified powder and natural rubber resin in an open mill to obtain composite rubber particles; heating the composite rubber particles in a non-oxidizing atmosphere of 500-700 DEG C, crushing them in a crusher and then sieving them to obtain composite powder; and magnetizing the composite powder in a magnetic field to obtain magnetic composite powder.

7. The preparation method according to claim 6, characterized in that: The oil-tea camellia shell, modified powder and natural rubber resin are mixed and crushed in an open mill, and then granulated through a 30-200 mesh screen to obtain composite rubber particles.

8. A magnetic composite powder prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the magnetic composite powder prepared by the preparation method according to any one of claims 1 to 7 in the degradation of methylene blue wastewater.

Citation Information

Patent Citations

  • Method for preparing magnetic biochar

    CN108722371A

  • Acid-resistant camellia oleifera shell-based magnetic active carbon and preparation method thereof

    CN110538630A